(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
A total of 114 water samples collected from different parts of Bangladesh were analyzed for the level of reactive nitrogen species NO3 and NH3. Nitrate was determined in 20 surface water, 28 motorized deep tube well and 66 hand operated tube well samples. Ammonia was determined in 18 surface water, 14 deep tube well and 49 hand operated tube well samples. These sites were randomly selected. Nitrate levels were found to be generally low (below 3 mg/l) in 112 of the 114 samples tested, which is much below permissible level of 10 mg/l of drinking water in Bangladesh. Ammonia concentration was, however, found to be about 4 mg/l in majority of the samples tested which is higher than maximum permissible limit of 0.5 mg/l in drinking water. Possible reasons for low level of nitrate and relatively high level of ammonia in surface and ground water samples in Bangladesh is discussed DOI: http://dx.doi.org/10.3329/jbas.v38i1.20214 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 75-82, 2014